PEMBINAAN AKHLAKUL KARIMAH MELALUI PEMBELAJARAN AKIDAH AKHLAK DI MTS RIYADLATUL FALLAH PLANDAAN JOMBANG - Fanani, Achmad Hulam; Hosna, Rofiatul (EL-Islam, 2022)
Abstract: Moral development is the teacher's effort to foster students' morals so that they can apply good morals. In foster, a teacher must be able to provide guidance or directives and good examples to students in order for them to follow and apply them in everyday life. Especially moral teachers who have an important role in fostering student morals because in learning a moral there is material that discusses about morals. Students must also get coaching from other teachers because fostering student morals must be continuous in order for the student to gain a morality. This study aims to explain how MTs Riyadlatul Fallah Plandaan Jombang conduct moral development through learning aqidah morals. This research, use qualitative approach. Data or information obtained through activities Interviews, observation, and documentation. The data is then collected and analyzed in order to get a better understanding of certain phenomena and can draw conclusions. And accord to results research, the founding of morals at MTs Riyadlatul Fallah through learning aqidah morals aims to form students with good morals such as diligence in worship, politeness, and commendable character.